Alteration of Gut Microbiome and Correlated Amino Acid Metabolism Contribute to Hyperuricemia and Th17-Driven Inflammation in Uox-KO Mice - Song, Siyue; Lou, Yu; Mao, Yingying; Wen, Xianghui; Fan, Moqi; He, Zhixing; Shen, Yang; Wen, Chengping; Shao, Tiejuan (Frontiers in Immunology, 2022)
Although gut dysbiosis had been demonstrated to be an important factor affecting hyperuricemia (HUA) and gout, little is known for its potential mechanistic connections. In this study, Uox-KO mice model that with spontaneously developed pronounced HUA and urate nephropathy was used to explore the pathophysiologic mechanism of microbiota alterations in HUA and gout with integrated multi-omics analysis. 16S rRNA gene sequencing was performed to characterize the characteristic bacteria, and untargeted LC/MS analysis was applied to reveal the featured metabolites. Our results showed there was a significant shift in gut microbiota composition and function in Uox-KO mice compared to WT mice and apparent metabolomics differences between the two groups. Among them, amino acids metabolism appears to play a critical role. Correlation analysis further revealed that the characteristic metabolites were strongly influenced by the discrepant bacterial genera. Furthermore, impairment of intestinal integrity and profound alterations in the profile of solute carrier family resulted in dysregulation of amino acids transportation, which subsequently impacted serum uric acid level and CD4+ Th17 driven inflammation. Together, these data indicate that gut dysbiosis promotes purine metabolism disorder and inflammation in Uox-KO mice. Remodeling the gut microbiota is a promising strategy to combat HUA and gout.